Swenson pull-through procedure with total mesorectal excision for a rectosigmoid mesenteric lymphatic malformation - David Chang; Angela Kadenhe-Chiweshe, MD; Demetri Merianos, MD (Elsevier, 2020)
Image guided sclerotherapy has become increasingly popular in the past decade, as a less invasive, first line approach for intraabdominal lymphatic malformations, especially in cases where complete resection is not felt to be achievable, or the morbidity of attempting surgical resection is untenable. Sclerotherapy does not offer a cure, but has been used to effectively manage symptoms in many cases. While surgical management is historically preferred, especially when it is expected to be curative, it has often been relegated to cases of complications, such as volvulus or intestinal obstruction. Here we present the case of a 5-month old male, who presented with a rectosigmoid mesenteric lymphatic malformation, and underwent successful surgical treatment, via Swenson pull-through procedure, with total mesorectal excision, and colo-anal anastomosis. We illustrate with this case, that surgery should be routinely considered in discussions of first line therapy, and various surgical techniques can be employed to achieve cure.